Psoriatic arthritis screening: a systematic review and meta-analysis. (31st October 2018) - Iragorri, Nicolas; Hazlewood, Glen; Manns, Braden; Danthurebandara, Vishva; Spackman, Eldon
Abstract: Objective: To systematically review the accuracy and characteristics of different questionnaire-based PsA screening tools. Methods: A systematic review of MEDLINE, Excerpta Medical Database, Cochrane Central Register of Controlled Trials and Web of Science was conducted to identify studies that evaluated the accuracy of self-administered PsA screening tools for patients with psoriasis. A bivariate meta-analysis was used to pool screening tool-specific accuracy estimates (sensitivity and specificity). Heterogeneity of the diagnostic odds ratio was evaluated through meta-regression. All full-text records were assessed for risk of bias with the QUADAS 2 tool. Results: A total of 2280 references were identified and 130 records were assessed for full-text review, of which 42 were included for synthesis. Of these, 27 were included in quantitative syntheses. Of the records, 37% had an overall low risk of bias. Fourteen different screening tools and 104 separate accuracy estimates were identified. Pooled sensitivity and specificity estimates were calculated for the Psoriatic Arthritis Screening and Evaluation (cut-off = 44), Psoriatic Arthritis Screening and Evaluation (47), Toronto Psoriatic Arthritis Screening (8), Psoriasis Epidemiology Screening Tool (3) and Early Psoriatic Arthritis Screening Questionnaire (3). The Early Psoriatic Arthritis Screening Questionnaire reported the highest sensitivity and specificity (0.85 each). The I 2 for the diagnostic odds ratios varied between 76 and 90.1%. Meta-regressions were conducted, in which the age, risk of bias for patient selection and the screening tool accounted for some of the observed heterogeneity. Conclusions: Questionnaire-based tools have moderate accuracy to identify PsA among psoriasis patients. The Early Psoriatic Arthritis Screening Questionnaire appears to have slightly better accuracy compared with the Toronto Psoriatic Arthritis Screening, Psoriasis Epidemiology Screening Tool and Psoriatic Arthritis Screening and Evaluation. An economic evaluation could model the uncertainty and estimate the cost-effectiveness of PsA screening programs that use different tools.